2017
DOI: 10.7554/elife.28635
|View full text |Cite
|
Sign up to set email alerts
|

Gdf3 is required for robust Nodal signaling during germ layer formation and left-right patterning

Abstract: Vertebrate embryonic patterning depends on signaling from Nodal, a TGFβ superfamily member. There are three Nodal orthologs in zebrafish; southpaw directs left-right asymmetries, while squint and cyclops function earlier to pattern mesendoderm. TGFβ member Vg1 is implicated in mesoderm formation but the role of the zebrafish ortholog, Growth differentiation factor 3 (Gdf3), has not been fully explored. We show that zygotic expression of gdf3 is dispensable for embryonic development, while maternally deposited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 79 publications
2
57
0
Order By: Relevance
“…There has been evidence for the codependence of the Nodal and GDF1/3 gene families during early developmental processes in all main groups of vertebrates for some time, but their interactions were not clear. This has recently changed, as three independent groups using different approaches reported that the formation heterodimers between Nodal and GDF1/3 is necessary to activate the Nodal pathway (Bisgrove et al, 2017;Montague & Schier, 2017;Pelliccia et al, 2017).…”
Section: Evolution Of the Nodal-gdf1/3 Heterodimersmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been evidence for the codependence of the Nodal and GDF1/3 gene families during early developmental processes in all main groups of vertebrates for some time, but their interactions were not clear. This has recently changed, as three independent groups using different approaches reported that the formation heterodimers between Nodal and GDF1/3 is necessary to activate the Nodal pathway (Bisgrove et al, 2017;Montague & Schier, 2017;Pelliccia et al, 2017).…”
Section: Evolution Of the Nodal-gdf1/3 Heterodimersmentioning
confidence: 99%
“…The Nodal pathway is active during the pregastrulation and gastrulation stages of development (Shen, ; Zinski, Tajer, & Mullins, ) and is responsible for multiple fundamental processes such as mesoderm induction and patterning, endoderm function, neural patterning, establishment of left‐right asymmetry, dorsal‐ventral axis specification, anterior–posterior axis formation, and maintenance of undifferentiated embryonic stem cells (Conlon, Lyons, Takaesu, Barth, & Kispert, ; Feldman et al, ; Jones et al, ; Schier, ; Shen, ). Recently, three independent groups have shown that in vertebrates Nodal needs to form heterodimers with the GDF1/3 protein, encoded by another member of the TGF‐β superfamily, to activate the signaling pathway (Bisgrove, Su, & Yost, ; Montague & Schier, ; Pelliccia, Jindal, & Burdine, ). To gain insights into the evolutionary history of the Nodal pathway, Opazo and Zavala () studied the evolutionary history of the GDF1/3 gene family and found that the vast majority of vertebrates have a single GDF1/3 ortholog in their genome.…”
Section: Introductionmentioning
confidence: 99%
“…There has been evidence for the co-dependence of the Nodal and GDF1/3 gene families during early developmental processes in all main group of vertebrates for some time, but their interactions were not clear. This has recently changed, as three independent groups using different approaches reported that the formation heterodimers between Nodal and GDF1/3 is necessary to activate the Nodal pathway (Bisgrove et al, 2017;Montague and Schier, 2017;PellicciaJ.L. et al, 2017).…”
Section: Evolution Of the Nodal-gdf1/3 Heterodimersmentioning
confidence: 99%
“…The Nodal pathway is active during the pre-gastrulation and gastrulation stages of development (Shen, 2007;Zinski et al, 2018) and is responsible for multiple fundamental processes such as mesoderm induction and patterning, endoderm function, neural patterning, establishment of left-right asymmetry, dorsal-ventral axis specification, anteriorposterior axis formation and maintenance of undifferentiated embryonic stem cells (Conlon et al, 1994;Jones et al, 1995;Feldman et al, 1998;Schier, 2003;Shen, 2007). Recently, three independent groups have shown that Nodal needs to form heterodimers with the GDF1/3 protein, encoded by another member of the TGF-β superfamily, to activate the signaling pathway (Bisgrove et al, 2017;Montague and Schier, 2017;PellicciaJ.L. et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish mesendoderm is patterned by two Nodal signals, Cyclops and Squint 7,40 . The physiologically relevant ligands are heterodimers between Cyclops or Squint and a third TGFb family member, Vg1 [44][45][46] . Gradient formation is initiated by secretion of Nodal ligands from the extraembryonic yolk syncytial layer (YSL), below the embryonic margin.…”
Section: Introductionmentioning
confidence: 99%